Stroke volume during exercise: interaction of environment and hydration - Gonzalez-Alonso, J.; Mora-Rodriguez, R.; Coyle, E. F. (American Journal of Physiology - Heart and Circulatory Physiology, 2000)
Euhydrated and dehydrated subjects exercised in a hot and a cold environment with our aim to identify factors that relate to reductions in stroke volume (SV). We hypothesized that reductions in SV with heat stress are related to the interaction of several factors rather than the effect of elevated skin blood flow. Eight male endurance-trained cyclists [maximal O2 consumption (O2 max) 4.5 ± 0.1 l/min; means ± SE] cycled for 30 min (72% O2 max) in the heat (H; 35°C) or the cold (C; 8°C) when euhydrated or dehydrated by 1.5, 3.0, or 4.2% of their body weight. When euhydrated, SV and esophageal temperature (Tes 38.2-38.3°C) were similar in H and C, whereas skin blood flow was much higher in H vs. C (365 ± 64% higher; P < 0.05). With each 1% body weight loss, SV declined 6.4 ± 1.3 ml (4.8%) in H and 3.4 ± 0.4 ml (2.5%) in C, whereas Tes increased 0.21 ± 0.02 and 0.10 ± 0.02°C in H and C, respectively (P < 0.05). However, reductions in SV were not associated with increases in skin blood flow. The reduced SV was highly associated with increased heart rate and reduced blood volume in both H (R = 0.96; P < 0.01) and C (R = 0.85; P < 0.01). In conclusion, these results suggest that SV is maintained in trained subjects during exercise in euhydrated conditions despite large differences in skin blood flow. Furthermore, the lowering of SV with dehydration appears largely related to increases in heart rate and reductions in blood volume.